“Estrategias activas para el b-learning” - Ayala Chusin, Mercy Yolanda (2022)
These years and after the pandemic, education is heading for changes, which break borders with new knowledge in the world, implementing strategies that are adapted with ICTs uses, (information and communication technologies) the same ones that have had a big impact in the educational process. Before it, in the teaching-learning process teachers must apply innovative strategies, which will need to be focused on critical thinking development, which will contribute to cognitive development, procedural and attitudinal skills mainly guided in virtual modality or b - learning. In front of this, teachers in their pedagogical process have focused their classes on traditionalist practices, mostly due to unknown technology application. currently teachers do not use active strategies and do not contribute to the students’ cognitive development in the learning process, becoming rote and bookish, falling back on the traditional. This research main is to determine the active strategies for B-learning students’ generation at sixth grade from "Vicente León" Elementary School, located in Latacunga - Cotopaxi province. The methodology was based on starting from the interpretive approach which allow to understand the social context reality in its nature. In this sense, qualitative was used because was developed in four stages: preparatory, field, analytical and informative, this research is descriptive and documentary. Inductive was the applied method, the technique is the interview and the instrument is the interview guide which was directed to Vicente León teachers, the information collected allowed to demonstrate the real problems that occur inside the educative institution. The results are evidence that show the lack of knowledge in ICTs uses by the teachers, in addition, the lack of tools and technological inputs by the students was identified too. Also, was possible to notice the teachers’ interest have for training and self-preparation with their own financing, in order to be on par with the students called digital natives, being noted that in the course of time, virtually had a big impact in the educational process, breaking barriers of space and time where was possible to reach different places with learning. However, do not discard the need to deepen into active strategies such as b-learning, because promote teaching-learning processes. This project will contribute with updated information and relevant guidance on technological ways uses and active strategies, which will motivate teachers and future professionals to manage ICTs, for better performance in the classroom.